2018
DOI: 10.1002/lio2.142
|View full text |Cite
|
Sign up to set email alerts
|

Association of alterations in smell and taste with depression in older adults

Abstract: ObjectiveExamine the relationship between depression and changes in smell or taste.Study DesignCross‐sectional analysis of 2011–2012 and 2013–2014 National Health and Nutrition Examination Survey (NHANES).MethodsWe examined 5,275 adults ≥40 years old who completed smell and taste questionnaires as well as a validated depression assessment instrument, the Patient Health Questionnaire (PHQ‐9). Analyses incorporated sampling weights to account for the complex sampling design and associations were analyzed using m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
63
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(71 citation statements)
references
References 42 publications
(119 reference statements)
4
63
0
Order By: Relevance
“…19 Chemosensory dysfunction, outside of the context of COVID-19, has been previously shown to be associated with decreased quality of life as well as anxiety and depression. 30,31 It is also described that depression may lead to OD. 32 However, in the setting of the COVID-19 pandemic and wide public recognition of the potential lethality of SARS-CoV-2 infection, we report here that the severities of classic and worrisome symptoms of COVID-19-such as fever, cough or SOB-were not associated with emotional disturbance while chemosensory dysfunction was.…”
Section: Covid-19 Remains a Global Threat To Public Health Having Afmentioning
confidence: 99%
“…19 Chemosensory dysfunction, outside of the context of COVID-19, has been previously shown to be associated with decreased quality of life as well as anxiety and depression. 30,31 It is also described that depression may lead to OD. 32 However, in the setting of the COVID-19 pandemic and wide public recognition of the potential lethality of SARS-CoV-2 infection, we report here that the severities of classic and worrisome symptoms of COVID-19-such as fever, cough or SOB-were not associated with emotional disturbance while chemosensory dysfunction was.…”
Section: Covid-19 Remains a Global Threat To Public Health Having Afmentioning
confidence: 99%
“…Loss of the ability to taste and smell has a direct impact on safety and quality of life [2]. For example, plenty of recent reports suggest that individuals with taste and smell disorders are more likely to have depressive symptoms [3][4][5][6]. A recent study reported potentially decreased sexual desire among subjects with smell impairment and depressive symptoms [7].…”
Section: Introductionmentioning
confidence: 99%
“…There was, however, no significant result during the pairwise group comparisons for this variable. Prior research showed a strong association between subjective smell impairment and major depression (Hur et al 2018). Furthermore, a review by Rochet et al argues that measured olfactory identification is often not impaired in depression (Rochet et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Third, variables of cognitive decline, namely verbal memory and executive control, in addition to depressive symptoms, age, and gender, will be compared between formed groups of awareness of olfactory functioning in the study population. The awareness of one's own olfactory functioning is likely to be not only influenced by symptoms of depression and age, but also by cognitive decline, in a way that depressed patients tend to underestimate their abilities (Hur et al 2018;Rochet et al 2018), while the contrary is expected with increasing age and cognitive decline (Nordin et al 1995;Devanand et al 2000;Wehling et al 2011).…”
Section: Introductionmentioning
confidence: 99%